Field studies on the effects of under sleeper pads in lateral resistance of railway - Armin Monir Abbasi (Iranian Society of Structrual Engineering (ISSE), 2016)
Under sleeper pads are used in several areas, specially, in places where transfer of vibrations to the surrounding areas should be limited. Beside of all advantages of this elements in the field of reducing costs of repair and maintenance of railway, improvement of line geometry, decreasing the thickness of required ballast, reduction of vibrations and disturbing noises coming from passing trains and increasing trip convenience, use of these pads according to thickness and hardness of them could be effective in lateral resistance. Based on international evaluations in the field of under sleeper pads, results of influence of under sleeper pads in lateral resistance  of railway are various, because of different reasons including: contact quality and compression of ballast grains, ballast thickness, distance between sleepers and different test for estimating the lateral resistance, therefore application of these pads specially in mountainous ways that lateral resistance is important, influence of these pads must be cleared. So in this field of study, lateral resistance of railway is measured by Single Tie Push Test. In this study 150 polyurethane under sleeper pads with two different stiffness which were produced by Getzner Company (specialize in vibration insulation in the rail), used in real line. Results of this field examinations show utilization of these elements under the sleepers increase 9.6% for the lateral resistance when SLB 3007 G (which are stiffer) attached in comparison to sleepers without pad and 2.54%  decrease when SLB 1308 G attached in comparison to sleepers without pad. However decrease in hardness, results in increasing rate of lateral resistance reduction.